Evektivitas Sanksi Pidana Terhadap Praktik Pengganda Uang - Widianingtyas, Indah (UM Purwokerto Press, 2024)
The practice of money multipliers is a common phenomenon in Indonesia. This practice exploits public trust to achieve personal gain. The negative effects of this practice include financial loss and exploitation. Indonesian criminal law has regulated fraud and embezzlement, which can be applied to ensnare money multiplier shamans. However, the effectiveness of criminal law in overcoming this practice is still questionable. However, the effectiveness of criminal law in dealing with this practice is still unclear. This study aims to analyze the effectiveness of criminal law on the practice of money multiplier shamans. This study uses a normative legal analysis method using a doctrinal and empirical approach. The results of the study indicate that criminal law has the potential to be an effective instrument in overcoming the practice of money multiplier shamans. However, there are several factors that can hinder the effectiveness of criminal law, such as Lack of public awareness of criminal law, Difficulty in proof. To increase the effectiveness of the law in responding to money multiplier practices, steps are needed such as increasing public awareness of the law, increasing the capacity of law enforcement officers, and strengthening the law enforcement system.